Bieszczadnik . gazetka Federacji Robotników, Rolników i innych grup zawodowych Bieszczadów NSZZ "Solidarność", no. 1, 1981 - [ed. zespół strajkowy] ([s.n.], 1981)
Creation and circulation: For internal use; After the introduction of the Martial Law publication suspended. Republished in 1982